Show by induction that sum_n(r*3^(r-1))=1/4+(3^n/4)*(2n-1) for n>0

Base Case n=1sum_1(r3^(r-1))=13^0=1=1/4+(3^1/4)(2-1)=1/4+3/4=1
Assume true for n=ki.e. sum_k(r
3^(r-1))=(3^k/4)(2k-1)
then for n=k+1sum_(k+1)(r
3^(r-1))= sum_k(r3^(r-1))+(k+1)3^k =(3^k/4)(2k-1)+(k+1)3^k =(3^k/4)(2k-1+4k+4)=(3^k/4)(6k+3)=(3^(k+1)/4)(2k+1)=(3^(k+1)/4)(2*(k+1)-1)
Therefore by inductionsum_n(r3^(r-1))=1/4+(3^n/4)(2n-1) for n>0

Related Maths A Level answers

All answers ▸

differentiate 4x^3 + 3x


Find dy/dx of the curve x^3+5xy-2y^2-57=0


A curve has equation y=x^2 + 2x +5. Find the coordinates of the point at which the gradient is equal to 1.


Differentiate: y=12x(2x+1)+1/x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences